Engineering and legal considerations for decommissioning of offshore oil and gas infrastructure in Australia. (1st February 2017) - Chandler, John; White, David; Techera, Erika J.; Gourvenec, Susan; Draper, Scott
Abstract: Offshore oil and gas platforms, pipelines and other ancillary offshore infrastructure are aging in Australia and current regulatory frameworks favour complete removal at the end of life. However, evidence indicates that artificial reefs have formed around some of these structures and their removal could cause more harm than good. Furthermore, other perceived social, environmental and economic benefits of a total removal policy may not be warranted. The Australian regulator (NOPSEMA) is currently exploring the possibility of supporting an in situ decommissioning policy, in which alternatives to full removal such as leaving in situ, partial removal or nearby relocation may be adopted if demonstrated to be the preferable approach. This will necessarily involve changes to law and policy but such amendments must be evidence-based. The evidence needed will largely involve the disciplines of engineering and natural sciences, but also fields such as environmental management, economics, social sciences and law. If Australia were to progress an in situ decommissioning policy shift, research will be needed across all of these areas in the specific national context. This paper commences by outlining emergent engineering knowledge, showing the general conservatism of current methodologies available to assess the integrity of decommissioned offshore facilities. Thereafter, the particular legal environment in Australia is explored. This article contributes to the growing body of literature on in situ decommissioning but in setting a multi-disciplinary research agenda takes a more holistic approach. Highlights: Offshore infrastructure is aging in Australia and regulations favour complete removal. NOPSEMA is exploring a possible in situ decommissioning policy. Australia is uniquely placed to show leadership in adopting innovative approaches. Evidence-based law and policy is needed to ensure engineering knowledge is embedded. A holistic approach, with cross-industry and multi-disciplinary outcomes is needed.